Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Pegawai Dinas Komunikasi Dan Informatika Kota Batu - Setyowati, Ninik Sri (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Abstract: From the results of this thesis research work motivation and work environment partially have a positive and significant effect on job satisfaction. This means that work motivation and work environment affect employee perceptions of job satisfaction. Good job satisfaction increases employee desires can be an intervening variable for motivation and work environment on employee performance. Work motivation and work environment have a higher coefficient value when it directly affects performance, compared to when through job satisfaction as an intervening variable. The purpose of this study was to determine the effect of simultaneous, partial and dominant work motivation, work environment on performance and job satisfaction as mediating variables for employees of the Dinas Komunikasi dan Informatika,  Batu City. The population in this study were all employees totaling 82 employees using the census method. By using path analysis.Suggestion for research is that organizations must be more intense in paying attention to work motivation and an adequate work environment on the performance of their employees so that job satisfaction is quickly achieved. Thus the organizational goals will be achieved as well as expected. Keywords: Work Motivation, Work Environment, Performance, Job Satisfaction